Decentralized Service Delivery for the Poor - World Bank (Washington, DC, 2012)
This report on the decentralized service delivery for the poor is structured in two volumes. Volume one is a cross-sectoral report, the core report. The first part includes the program and performance overview which describes the programs (including their poverty goals) and their process of decentralization, the overview of expenditures, the access of the poor to these services, and the evidence on the quality of services. The second part of the core report is on the institutional dimensions of decentralized service delivery which includes the World Development Report (WDR) 2004-type framework of accountability, adapted to the situation in Mexico. Volume two contains the sectoral pieces. For this report-the third phase of a programmatic series of studies on poverty in Mexico-Mexico's social cabinet requested that the Bank analyze service delivery of a specific list of programs that are essential to the government's development strategy in the context of decentralization. The elements of the government's strategy considered here-basic education, health care for the population without social security coverage, local social infrastructure, and local rural development-all aim directly or indirectly to reduce poverty. Both social and economic services shape the opportunities of poor people. Social services contribute to human capital formation and risk management, while economic services shape access to markets. The analysis presented in this report does not pretend to be exhaustive of decentralized service delivery for the poor. Important areas for future research include the following: (i) analysis of the compliance of the law or of the detail regulations in programs; (ii) systematic comparisons of state interventions in the sectors analyzed in this report; (iii) analysis of the implications and requirements to implement per capita funding in health and education, and freedom to choose providers; and (iv) systematic compilation of information at the state and municipal level on the performance of the programs.